2021
DOI: 10.1108/ijlm-04-2021-0231
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic and technological new normal in supply chain management: lessons from COVID-19 pandemic

Abstract: PurposeThis paper explores the new normal activities and strategic responses of the service industry towards the challenges created by the coronavirus disease 2019 (COVID-19) outbreak and other constructs and validates the measurement scale for socio-economic and technological new normal activities following lockdown and social distancing practices.Design/methodology/approachFirst, structured interviews with 28 participants helped us generate items and develop survey instruments for cross-sectional data collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…property management systems in hotels or lodging companies) ( Farías and Cancino, 2021 ); and cybersecurity solutions (e.g. anti-cyber-crimes programs in service firms operating in tourism) ( Ajmal, Khan, Shad, AlKatheeri and Jabeen, 2021 ). Social media are the most adopted network technologies by tourism ( Ajmal et al, 2021 ; del Vecchio, Malandugno, Passiante and Sakka, 2021 ; Gössling, 2020 ; Ianioglo and Rissanen, 2020 ; Lemmi and Deri, 2020 ; Varelas et al, 2021 ) and hospitality firms (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…property management systems in hotels or lodging companies) ( Farías and Cancino, 2021 ); and cybersecurity solutions (e.g. anti-cyber-crimes programs in service firms operating in tourism) ( Ajmal, Khan, Shad, AlKatheeri and Jabeen, 2021 ). Social media are the most adopted network technologies by tourism ( Ajmal et al, 2021 ; del Vecchio, Malandugno, Passiante and Sakka, 2021 ; Gössling, 2020 ; Ianioglo and Rissanen, 2020 ; Lemmi and Deri, 2020 ; Varelas et al, 2021 ) and hospitality firms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…anti-cyber-crimes programs in service firms operating in tourism) ( Ajmal, Khan, Shad, AlKatheeri and Jabeen, 2021 ). Social media are the most adopted network technologies by tourism ( Ajmal et al, 2021 ; del Vecchio, Malandugno, Passiante and Sakka, 2021 ; Gössling, 2020 ; Ianioglo and Rissanen, 2020 ; Lemmi and Deri, 2020 ; Varelas et al, 2021 ) and hospitality firms (e.g. hotels or lodging companies) ( Amoah et al, 2021 ; del Vecchio et al, 2021 ; Farías and Cancino, 2021 ; Ianioglo and Rissanen, 2020 ; Lemmi and Deri, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, new normal activities are constantly emerging in which companies are deploying crisis strategies to retain their stakeholders and business. Companies are re-opening swiftly, focusing more on digital transformations, implementing digital platforms/tools for improved consumer services and ease in working, to name a few operational changes [287]. Besides these technical developments, researchers are emphasizing the need for research in COVID19-induced brain dysfunction (CIBD) to improve the mental health of large populations of infected/uninfected individuals [288].…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Some scholars found a negative influence on physical health and social life during the pandemic (Mujahid et al, 2021). Other research on the impact of COVID-19 on employees has shown that the reduction of economic activities during the pandemic resulted in a rise in poverty and unemployment and hence affected workers (Ajmal et al, 2021a;2021b). Scholars have also found the development of inequality in unemployment (M€ ohring et al, 2020).…”
Section: Introductionmentioning
confidence: 99%